Association between Mycoplasma genitalium and pelvic inflammatory disease: systematic review (Research, Society and Development, 2023)
The Mycoplasma genitalium has become one of the most emerging sexually transmitted infections worldwide. When installed, it may be associated with complications such as cervicitis, non-gonococcal urethritis, and endometritis. Furthermore, there is also evidence of the emergence of pelvic inflammatory disease in patients with Mycoplasma genitalium, although there is a scarcity of data on this. Therefore, we aimed to evaluate the existence of an association between Mycoplasma genitalium and pelvic inflammatory disease or pelvic pain. This is a systematic review, developed in January 2023, considering cohort studies, clinical trials, and cross-sectional studies. The PubMed and CINAHL databases were used, as well as the BVS and Google Scholar virtual libraries. Also, the AskMEDLINE platform was searched, using the guiding question. The studies were limited to Portuguese, English and Spanish, and published between 2012 and 2022. Of the 2,413 works found, only five were selected for the final sample. All findings showed an association between Mycoplasma genitalium and pelvic inflammatory disease, although this relationship was quite variable (2.1%-38%). Pelvic pain was also present in the patients tested, although an asymptomatic or oligosymptomatic condition has also been reported in many cases. Although Mycoplasma genitalium represents an important portion of the infections that cause pelvic disease, Chlamydia trachomatis is still the main cause of it. However, new investigations need to be designed in an attempt to elucidate the relationship between the infection and other sexually transmitted infections and common clinical manifestations.